Appunti sulla rappresentazione spaziale. Il Veneto disegnato da Giosetta Fioroni e l’Emilia fotografata da Cuchi White - Marsi, Simone (Status Quaestionis, 2024)
The aim of this essay is to investigate how two female artists, Giosetta Fioroni and Cuchi White, interpreted and represented two Italian real places: the Venetian countryside around the Piave River, and the places around the Via Emilia, an ancient Italian road still essential for communications and economy nowadays. Starting from Westphal’s reflection on geocriticism, this article analyses the book Attraverso l’evento (1988), which contains both Andrea Zanzotto’s poems and Giosetta Fioroni’s illustrations. The relationship between words and images re-creates a Venetian countryside as a place of ancestral memory, where the nature is inhabited by fabulous creatures belonging to old fairy-tales. The second part of this essay analyses Cuchi White’s photographs. These images, as her famous trompe l’oeil, represent both a real space and the way in which the human being perceives, lives, and creates the space.